2018
DOI: 10.1111/ijfs.13927
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of beef lung protein powder as a functional ingredient to enhance protein and iron content of fresh pasta

Abstract: Summary Beef lungs are an underutilised co‐product of the meat industry that could be used as an ingredient to supplement the protein content of cereal foods. Beef lung powder (BLP) had a protein content of 87% (dry weight basis), an amino acid score of 1, and contained 1 mg g−1 iron. Fresh semolina pasta was used as a model food, and BLP was incorporated up to 20%. Incorporation of 10% BLP improved the indispensable amino acid score of the pasta from 0.48 to 0.91. At that level of incorporation, higher cookin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…Petitot et al. (2010) reported that the in vitro glycemic index of pasta is not affected by supplementing pasta with 35% split pea / faba bean flour, while other studies reported that the fortification with beef lung protein powder at 10%–20% lowered the glycemic response in pasta (Jayawardena et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Petitot et al. (2010) reported that the in vitro glycemic index of pasta is not affected by supplementing pasta with 35% split pea / faba bean flour, while other studies reported that the fortification with beef lung protein powder at 10%–20% lowered the glycemic response in pasta (Jayawardena et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence of a change in pasta structure, this was not sufficient to alter the in vitro starch digestion extent, which could be seen as a positive impact of WBPC of not increasing starch digestion. Petitot et al (2010) reported that the in vitro glycemic index of pasta is not affected by supplementing pasta with 35% split pea / faba bean flour, while other studies reported that the fortification with beef lung protein powder at 10%-20% lowered the glycemic response in pasta (Jayawardena et al, 2019).…”
Section: Starch Digestion Of Wbpc Pastamentioning
confidence: 98%
“…Offal cuts are good sources of protein, and notably very valuable for its nutrition (van Heerden & Morey, 2014). Liver is high in vitamin A, iron, zinc, vitamin B, vitamin C, vitamin D, copper, and fatty acids (Khalil et al, 2018) and lungs contain high levels of protein and bioavailable iron (Jayawardena et al, 2018). However, edible offal are highly perishable because of the high content of nutrients for microbial growth (Custódio et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the International Journal of Food Science and Technology paid special attention to these topics. A lot of papers were published, including the utilisation of novel ingredients to reduce meat fat (Glisic et al , ), novel processes for meat tenderisation (Wang et al , ), new aspects of novel bioactive compounds of meat (Jayawardena et al , ; O’Flaherty et al , ; Xing et al , ) and the detection of adulterant and impurities in meat for food safety (Iammarino et al , ; Qin et al , ).…”
mentioning
confidence: 99%
“…In recent years, the International Journal of Food Science and Technology paid special attention to these topics. A lot of papers were published, including the utilisation of novel ingredients to reduce meat fat (Glisic et al, 2019), novel processes for meat tenderisation (Wang et al, 2019), new aspects of novel bioactive compounds of meat (Jayawardena et al, 2019;O'Flaherty et al, 2019;Xing et al, 2019) and the detection of adulterant and impurities in meat for food safety (Iammarino et al, 2017;Qin et al, 2019). This Special Issue, entitled 'Recent advances in meat products quality & safety improvement and assurance', aims to provide information on recent research focused on the improvement of meat and meat products' safety and quality.…”
mentioning
confidence: 99%